Mammographic interpretation in Vietnam: Tailored educational strategies are needed to increase clinicians' expertise. Issue 5 (10th September 2020) - Caspar, Felix; Copps, Emily; Diplas, Adrienne; Hackney, Logan; Jackson, Kyle; Kearins, Imogen; Lynch, Marcus; McPherson, Dominique; Pisconeri, Bellah; Purkiss, Zara; Thomas, Lucy; Colley, Brooke; et al.
Abstract: Aim: Breast cancer incidence is rapidly increasing throughout South East Asia, highlighting the need for high‐quality early diagnosis and treatment. This study aims to investigate the efficacy of mammography detection in Hanoi and Ho Chi Minh City (HCMC), Vietnam, using data from Australian radiologists as a benchmark; factors that influence performance will be highlighted. Methods: A total of 53, 35 and 52 clinicians from Australia, HCMC and Hanoi, respectively, examined and diagnosed a test set of 60 mammograms, 20 of which contained cancers. Each clinician completed an accompanying questionnaire establishing demographic and experiential characteristics. The performance metrics of specificity, sensitivity, area under the receiver operating characteristic curve (AUC), location sensitivity and Jackknife free‐response ROC (JAFROC) figure of merit were used to evaluate clinicians performance. Mann‐Whitney and Kruskal‐Wallis statistical methods were employed to establish significance. Results: Vietnamese radiologists demonstrated significantly lower sensitivity, AUC, lesion sensitivity and JAFROC scores compared to Australian radiologists. There was no difference in performance between clinicians from Hanoi and HCMC. However, certain performance features (older and more experienced clinicians compared with their younger, less experienced counterparts, readers who read more compared with fewer mammograms per week, clinicians with greater radiological experience and clinicians that completed a fellowship) demonstrated significantly better performances. Conclusions: The significant difference in diagnostic efficacy of mammograms between Vietnam and Australia identifies the need for improvements in breast radiology training, management and practice. Cost‐effective solutions are available that can improve the reading efficacy of clinicians, and consequently health outcomes for Vietnamese women. Abstract : Breast cancer incidence is rapidly increasing throughout South East Asia, highlighting the need for early diagnosis. Vietnamese radiologists demonstrate lower diagnostic performances than Australian radiologists. However, within Vietnam, older, more experienced clinicians display greater diagnostic skills than their younger less experienced counterparts. A system for improving reading ability is proposed.